DETERMINATION OF PYROGALLOL RED ON A GLASSY CARBON ELECTRODE MODIFIED WITH GOLD FILM AND CYSTEAMINE BY ADSORPTION VOLTAMMETRY (AdsV). POSSIBLE USE AS ELECTROCHEMICAL SENSOR - Bolaños, Karen (2015)
Interaction pyrogallol red (RP) on glassy carbon electrode surface modified gold film (AUF)and cysteamine (cis) was studied. Bearing in mind the order of the modification, it was foundthat the response of oxidation of RP showed higher current to the electrode modified withgold film electro-deposited on cysteamine glassy carbon (GC/Cis /AuF/E), which allowsthe RP oxidation potential of 0.48 V at pH 3.25. Electrochemical devices, such as pH, scanrate (Ʋ), adsorption potential (Eads) and adsorption time (tads) parameters were optimized toyield values: pH 3.25; Ʋ 75.50mV s-1; Eads0.10 V and tads60 s respectively. The calibrationcurve linearity reached a range between 2.00 x 10-7and 15.14x10-7mol L-1. The detection limit(3S/m) was 1.20 x 10-7mol L-1 and relative standard deviation for measurements of sevenequal RP 5.0 x 10-4mol L-1 was 1.01%.